Analysis Of the Results of Surgical Treatment of Adults with Rhinocerebral Mucoromycosis (Texas Journal of Medical Science, 2024)
This article summarizes the experience of surgical treatment of mucormycosis of the rhinocerebral type. The work is based on the results of complex treatment of 134 patients with mucoromycosis of the rhinocerebral type, who were treated in the department of ENT and maxillofacial surgery of the MMC of the Andijan region, as well as in the department of neurology of the Republican Center for Emergency Medicine of the Andijan branch from 2019 to 2022, aged from 45 to 65 years. Of these, 33 (24.6%) patients were male and 101 (75.3%) were female. The main affected areas were the nasal cavity, the maxillary sinus and the upper jaw of the facial skeleton (118 patients (88.1%)). In the long-term period from 3 months to 2 years, 52 (41.9%) patients showed good, 59 (47.6%) satisfactory and 13 (10.5%) unsatisfactory results